Feedback : an exploratory narrative analysis - Chatterjee, Ayan (2019)
The focus of the study was to establish that feedback is a complex construct and that looking at it as a whole might give us a chance to use it more efficiently. The effect of feedback on motor activity is manifold; the nature of the feedback, the timing of when feedback is given, the individual who gives the feedback, the frequency of feedback, the reason behind why feedback is given as well as the type of feedback all influence motor learning and performance. The aim of this study was to examine how coaches and athletes perceive and understand different effects, and types of feedback; how the purpose, timing, context or the content of feedback influences performance. A qualitative narrative design was adopted for the study. The study sampled 6 participants out of whom 5 participants had experiences as both athletes and as coaches while 1 participant was only a former athlete. Semi-structured interviews were conducted, and the data was analysed with the help of Atlas.ti. A content analysis was conducted, and 2 main themes emerged as a result of selective coding, namely successful and unsuccessful feedback with 10 major codes. On further analysis it was found that 7 main codes such as who is giving the feedback, personality factors of the recipient, the types, the content, the purpose, the timing and the strategy of feedback seemed to be leading to successful feedback while 3 other codes such as, how feedback is received, environmental factors and how ready one is to receive feedback also influenced the success of feedback but that all are important parts that need to be investigated further. Finally, the limitations the possible explanations for divergent results and future scope are also discussed.